2021
DOI: 10.5194/cp-2021-122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late Paleocene CO<sub>2</sub> drawdown, climatic cooling, and terrestrial denudation in the southwest Pacific

Abstract: Abstract. Late Paleocene deposition of an organic-rich sedimentary facies on the continental shelf and slope of New Zealand and eastern Australia has been linked to short-lived climatic cooling and terrestrial denudation following sea-level fall. Recent studies have confirmed that the organic matter in this facies, termed Waipawa organofacies, is primarily of terrestrial origin, with a minor marine component. It is also unusually enriched in δ13C. In this study we aim to determine the cause or causes of this e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…We attribute this discrepancy to the complex organic matter source changes across the K-Pg boundary. This could include a transient pulse of reworked 13 C-enriched kerogen, similar to what has complicated PETM CIEs (Inglis et al, 2019) or strongly altered terrestrial organic matter as observed in the same section during the Paleocene Carbon Isotope Maximum (or Waipara Event) as documented by Hollis et al (2022). Although it is unclear what the specific source of 13 C-enriched organic matter would have been, the impact of reworked organic matter on the fidelity of the bulk TOC carbon isotopic record has been documented previously (Carmichael et al, 2019).…”
Section: Bulk Organic Mattermentioning
confidence: 77%
“…We attribute this discrepancy to the complex organic matter source changes across the K-Pg boundary. This could include a transient pulse of reworked 13 C-enriched kerogen, similar to what has complicated PETM CIEs (Inglis et al, 2019) or strongly altered terrestrial organic matter as observed in the same section during the Paleocene Carbon Isotope Maximum (or Waipara Event) as documented by Hollis et al (2022). Although it is unclear what the specific source of 13 C-enriched organic matter would have been, the impact of reworked organic matter on the fidelity of the bulk TOC carbon isotopic record has been documented previously (Carmichael et al, 2019).…”
Section: Bulk Organic Mattermentioning
confidence: 77%